3
$\begingroup$

I've been doing some calculus problems lately out of an old Russian book, and I came across something I didn't fully understand: One of the problems said that $$\lim_{x\to \infty} x(\sqrt{x^2+1} - x) = \frac{1}{2}$$ Could someone please explain to my why this is the case?

Thanks a lot.

$\endgroup$
7
  • $\begingroup$ thanks Semiclassical-typo on my part $\endgroup$
    – Shreyas B.
    Jun 18, 2016 at 22:17
  • 5
    $\begingroup$ First, multiply by $\sqrt{x^2+1}+x\over \sqrt{x^2+1}+x$. $\endgroup$ Jun 18, 2016 at 22:22
  • 3
    $\begingroup$ @DavidMitra Please put answers as answers, not as comments. $\endgroup$
    – user231101
    Jun 18, 2016 at 22:24
  • $\begingroup$ @ShreyasB. Use $(a-b)(a+b) = a^2 - b^2$ and multiply by $(1/x)\over(1/x) $ $\endgroup$
    – user312097
    Jun 18, 2016 at 22:27
  • $\begingroup$ Beware of old Russian books, otherwise you end up with problems like these....+1 $\endgroup$
    – imranfat
    Jun 18, 2016 at 23:09

6 Answers 6

7
$\begingroup$

When you get questions like this (i.e. a one-line limit with a radical), always consider multiplying both numerator and denominator by "something" to make it look nicer.

In this case, consider what would happen if you multiply both numerator and denominator by $\sqrt{x^2+1} + x$.

$\endgroup$
1
  • $\begingroup$ Got it, thanks GrancescoFrechi and David Mitra! $\endgroup$
    – Shreyas B.
    Jun 18, 2016 at 22:26
7
$\begingroup$

Mutiplying the numerator and denominator by $\sqrt{x^2+1}+x$ we get that $$\begin{align}\lim_{x\to \infty} x(\sqrt{x^2+1} - x) &=\lim_{x\to \infty} \frac{x(x^2+1-x^2)}{\sqrt{x^2+1}+x}\\ &=\lim_{x\to \infty} \frac{x}{|x|\sqrt{1+x^{-2}}+x}\\ &=\lim_{x\to \infty} \frac{1}{\sqrt{1+x^{-2}}+1} \end{align}$$ where we have used the fact that $|x|=x$ because the limit is as $x$ goes to infinity. From here the limit is easy to compute.

$\endgroup$
2
  • $\begingroup$ I might be missing something but did you drop a square root sign? I.e shouldn't it be $ 1/[\sqrt (1 + x ^{-2})+1]? Which is the same result of course. $\endgroup$
    – fleablood
    Jun 18, 2016 at 22:50
  • $\begingroup$ @fleablood Thanks. I fixed the error. $\endgroup$ Jun 18, 2016 at 23:05
3
$\begingroup$

Hint: Let $t=1/x^2$ and recall the definition of the derivative as a difference quotient.

$\endgroup$
3
$\begingroup$

One interesting thing to note is that:

$k=x\sqrt{x^2+1}-x^2$

Implies that

$x=\frac{k}{\sqrt{1-2k}}$

And you can then see how $k=\frac{1}{2}$ is the asymptote quite easily.

$\endgroup$
2
$\begingroup$

$\lim_{x\to\infty} x(\sqrt{x^2+1}-x)=\lim_{x\to\infty} \sqrt{x^4+x^2}-x^2$

$=\lim_{x\to\infty}\frac{(\sqrt{x^4+x^2}-x^2)(\sqrt{x^4+x^2}+x^2)}{\sqrt{x^4+x^2}+x^2}=\lim_{x\to\infty}\frac{x^4+x^2-x^4}{\sqrt{x^4+x^2}+x^2}$

$=\lim_{x\to\infty}\frac{x^2}{\sqrt{x^4+x^2}+x^2}=\lim_{x\to\infty}\frac{1}{\sqrt{1+\frac{1}{x^2}}+1}\rightarrow \frac{1}{2}$

$\endgroup$
1
$\begingroup$

Another approach based on Taylor expansions.

Consider $$y=x(\sqrt{x^2+1} - x)=x^2\left(\sqrt{1+\frac{1}{x^2}}-1\right)$$ and remember that, for small $y$, $\sqrt{1+y}=1+\frac{y}{2}-\frac{y^2}{8}+O\left(y^3\right)$. Replace $y$ by $\frac{1}{x^2}$ to get $$\sqrt{1+\frac{1}{x^2}}-1=\frac{1}{2 x^2}-\frac{1}{8 x^4}+O\left(\frac{1}{x^5}\right)$$ which makes $$y=\frac{1}{2}-\frac{1}{8 x^2}+O\left(\frac{1}{x^3}\right)$$ showing the limit and also how it is approched

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.